2003
DOI: 10.1038/sj.bjc.6601110
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of mitochondrial genome instability in human endometrial carcinomas

Abstract: To investigate the occurrence of somatic mitochondrial DNA (mtDNA) mutations in human primary endometrial carcinomas, we sequenced the D-loop region, the 12S and 16S rRNA genes of mtDNA of cancer tissues and their matched normal controls. About 56% (28 out of 50) of cases carry one or more somatic changes in mtDNA including deletion, point mutation and mitochondrial microsatellite instability (mtMSI), namely the change in length of short base-repetitive sequences of mtDNA. In particular, mtMSI was frequently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 12 publications
0
47
2
Order By: Relevance
“…In contrast to the present study, various somatic mutations ranging from 25 to 60% have been reported in mitochondrial coding regions in many cancers (Liu et al, 2003;Abu-Amero et al, 2005;Yin et al, 2010). The variant A10398G in the ND3 gene was reported as somatic mtDNA mutation in cancers of breast, colorectal and prostate (Canter et al, 2005;Zhu et al, 2005;AllalunisTurner et al, 2006), while the variant A8701G in the ATP6 gene was identified as somatic mtDNA mutation in the cancers of breast and thyroid (Tan et al, 2002;Abu-Amero et al, 2005).…”
Section: Discussioncontrasting
confidence: 49%
“…In contrast to the present study, various somatic mutations ranging from 25 to 60% have been reported in mitochondrial coding regions in many cancers (Liu et al, 2003;Abu-Amero et al, 2005;Yin et al, 2010). The variant A10398G in the ND3 gene was reported as somatic mtDNA mutation in cancers of breast, colorectal and prostate (Canter et al, 2005;Zhu et al, 2005;AllalunisTurner et al, 2006), while the variant A8701G in the ATP6 gene was identified as somatic mtDNA mutation in the cancers of breast and thyroid (Tan et al, 2002;Abu-Amero et al, 2005).…”
Section: Discussioncontrasting
confidence: 49%
“…According to last version of rCRS, D-Loop contains 5 CA repeats at np514-523 but our result showed dinucleotide microsatellite instability in this region. About 20% of cancer patients and 15% of BPH patients had CA deletion at this site which is about ten fold greater than endometrial carcinoma (Liu et al, 2003). Thus, it is likely that there are different mechanisms of mtDNA alterations and repair in different tissues during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have demonstrated the occurrence of high frequencies of somatic mtDNA mutations in endometrial (Liu et al, 2003) and ovarian carcinomas (Liu et al, 2001). In addition, we have also found that mtDNA copy number was significantly elevated in endometrial adenocarcinoma when compared with normal endometrial glandular epithelium (Wang et al, 2005).…”
mentioning
confidence: 99%